PENDIDIKAN KARAKTER DALAM KHAZANAH PENDIDIKAN - A Mualif (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2022)
Character education is essentially a struggle to maintain the survival of mankind so as not to fall into destruction. This has been the main concern of Muslim intellectuals from classical times to the present. In the treasury of the world of Islamic education get an extraordinary place and attention. It can be seen that Islam views education as a conscious effort to ground the teachings of Islam which in essence is to build the character of humanity as a whole (kaaffah), so that it becomes an ummatan wasathan (ideal ummah), khaira ummah (the best ummah) and Islam has a role to play. saving mankind from decline, by giving hudan (guidance), syifa' (antidote), mau'idzah (teachings that touch the heart), and mercy for all nature. All components of Islamic education: principles, goals, curriculum, teaching materials, educators, environment, and educational institutions are built on the moral values ​​of Islamic teachings. The cash characteristics are based on five main aspects, namely moral conscience; moral obligation; moral law (moral judgment); moral responsibility, and moral rewards. To answer this the author will refer to various books or books of Islamic literature and Islamic education, then describe and analyze them comprehensively, critically and objectively, and then conclude.